Оптимізація асортименту продукції підприємств овочівництва - Вініченко, Ігор Іванович; Vinichenko, Ihor; Шутько, Тетяна Ігорівна; Shutko, Tetiana; Ручанчина, К. В.; Ruchanchina, K. (Дніпровський державний аграрно-економічний університет, 2021)
Визначено, що раціональне використання ресурсів для досліджуваних підприємств галузі овочівництва полягає в мінімізації витрат під час вирощування овочів відкритого ґрунту, а проблема управління виробничими витратами полягає не скільки у їх розподілі та забезпечення мінімізації, стільки у встановленні їх доцільності й досягненні необхідної прибутковості в умовах конкурентного середовища. Встановлено, що скорочення витрат, формування максимально можливого прибутку та залучення платоспроможних покупців можливе за рахунок упровадження асортиментної політики овочевих підприємств, адже більшість з них формують асортимент вирощуваної продукції інтуїтивно, не застосовуючи методів економіко-математичного моделювання. Аргументовано, що оптимізацію асортименту овочів відкритого ґрунту необхідно здійснювати відповідно до перспектив розвитку підприємств, оскільки це дозволить забезпечити досягнення стійкої товарної пропозиції підприємства попиту на овочеву продукцію за ринковими та цінам. The article argues that the vegetable enterprises of Dnipropetrovsk region do not have enough funds for the reproduction process, which is accompanied by the use of additional reserves to reduce production costs, finding ways to more effectively carry out economic activities in general. The imperfection of the assortment policy of vegetable enterprises contributes to the formation of an irrational structure of production, loss of control over competitors and reduced efficiency of production activities. Efficient use of resources for the for the studied enterprises is to minimize costs while growing vegetables open ground, and the problem of managing production costs is not much in their distribution and software to minimize, as much in establishing their feasibility and achievement of desired profitability in a competitive environment. It is established that cost reduction, formation of the maximum possible profit and attraction of solvent buyers is possible due to introduction of assortment policy of the vegetable enterprises as the majority of them form the range of grown up products intuitively, without applying methods of economic and mathematical modeling. It is argued that the optimization of the range of open-ground vegetables should be carried out in accordance with the prospects of enterprise development, as this will ensure the achievement of a stable product supply of demand for vegetable products at market and prices. It is proposed to grow cabbage and tomatoes in the first year of the cycle for Famtsov LLC, in the second - sweet peppers, cucumbers and cabbage, in the third - tomatoes, cabbage and cucumbers. Adhering to the specified plan of crop rotations, the enterprise will receive for 3-year production cycle on 31766,15 UAH. from 1 hectare of vegetable crops. For Tandem-agro LLC in the first year it is advisable to grow tomatoes, cucumbers, cabbage, zucchini and onions, in the second - tomatoes, cucumbers, cabbage and onions, in the third - cucumbers and cabbage, tomatoes and zucchini. The company will receive UAH 41,719.17 for a 3-year production cycle from 1 hectare of vegetable crops. In the first year, Ecofild LLC should grow sweet peppers, potatoes, beets and cucumbers, in the second - tomatoes, cabbage, garlic and potatoes, in the third - garlic, cucumbers, cabbage and beets. The project plan of crop rotation will provide UAH 37,800.91 for a 3-year production cycle from 1 hectare of vegetable crops. In the first year of VPK-AGRO LLC it is expedient to grow cucumbers, table pumpkins, sweet peppers and potatoes, in the second year - cucumbers, zucchini and sweet peppers, in the third year - cabbage and tomatoes. Adhering to the specified plan of crop rotations, the enterprise will receive for 3-year production cycle on 50063 UAH from 1 hectare of vegetable crops.
Optimization of the range of products of vegetable enterprises
Keywords: асортимент; range; витрати; costs; галузева структура; industry structure; овочева продукція; vegetable products; оптимізація; optimization; сівозміна; crop rotation; підприємство; enterprise; прибуток; profit